Erinea formation on Quercus ilex leaves: anatomical, physiological and chemical responses of leaf trichomes against mite attack. - Karioti, Anastasia; Tooulakou, Georgia; Bilia, Anna Rita; Psaras, George K.; Karabourniotis, George; Skaltsa, Helen (Phytochemistry, 2011)
Structures on the surfaces of leaves, such as dense layers of non-glandular trichomes, strongly affect phylloplane mite activities. On the other hand the feeding of eriophyoid mites on leaf surfaces can cause hyperplasia of leaf trichomes (erinea formation). In many cases the hyperplasia is accompanied by the accumulation of pigments within trichome cells, causing an impressive red-brown colouration of the erineum. There is no information, however, on the structure of these pigments as well as on the chemical alterations in the phenolic content of plant trichomes in response to mite attack. Erinea formation on the abaxial surface of Quercus ilex leaves upon Aceria ilicis (Acari: Eriophyoidea) attack provides an excellent model on this topic. Differences in the structure and chemical composition of isolated trichomes derived either from healthy (normal trichomes) or mite attacked (hypertrophic trichomes) leaves were examined. Carbon investment was comparable between the two different trichome types, but the cell walls of the hypertrophic trichomes appeared thinner and did not contain microcrystalline cellulose. Observations under the fluorescence microscope showed that the emitted fluorescence was different between the two trichome types, indicating a different composition in fluorescencing phenolic compounds. The chemical analyses confirmed that hypertrophic trichomes contained higher concentrations of the feeding deterrents proanthocyanidin B3 and catechin, as well as of quercetin-3-O-glucoside, but lower concentrations of acylated flavonoid glycosides, than the normal ones. The results showed that the structural and functional changes in leaf trichomes upon mite attack may be an effort of the leaf to compensate the damage caused by the pest.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 21131012
Keywords: Fagaceae; Leaf trichomes; Mites; phenolics; Quercus ilex